Antibacterial Activity against Four Fish Pathogenic Bacteria of Twelve Microalgae Species Isolated from Lagoons in Western Greece - Chrysa Androutsopoulou; Pavlos Makridis (Microorganisms, 2023)
Microalgae may produce a range of high-value bioactive substances, making them a promising resource for various applications. In this study, the antibacterial activity of twelve microalgae species isolated from lagoons in western Greece was examined against four fish pathogenic bacteria (Vibrio anguillarum, Aeromonas veronii, Vibrio alginolyticus, and Vibrio harveyi). Two experimental approaches were used to evaluate the inhibitory effect of microalgae on pathogenic bacteria. The first approach used bacteria-free microalgae cultures, whereas the second approach used filter-sterilized supernatant from centrifuged microalgae cultures. The results demonstrated that all microalgae had inhibitory effects against pathogenic bacteria in the first approach, particularly 4 days after inoculation, where Asteromonas gracilis and Tetraselmis sp. (red var., Pappas) exhibited the highest inhibitory activity, reducing bacterial growth by 1 to 3 log units. In the second approach, Tetraselmis sp. (red var., Pappas) showed significant inhibition against V. alginolyticus between 4 and 25 h after inoculation. Moreover, all tested cyanobacteria exhibited inhibitory activity against V. alginolyticus between 21 and 48 h after inoculation. Statistical analysis was performed using the independent samples t-test. These findings suggested that microalgae produce compounds with antibacterial activity, which could be useful in aquaculture.